2019
DOI: 10.1523/jneurosci.0432-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reward Prediction Error Modulates Saccade Vigor

Abstract: Movement vigor, defined as the reciprocal of the latency from availability of reward to its acquisition, changes with reward magnitude: movements exhibit shorter reaction time and increased velocity when they are directed toward more rewarding stimuli. This invigoration may be due to release of dopamine before movement onset, which has been shown to be modulated by events that signal reward prediction error (RPE). Here, we generated an RPE event in the milliseconds before movement onset and tested whether ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Yet, we still observed a pronounced change in accuracy post-muscimol even for the 36% coherence condition, a finding that is better explained by a change in aspects of decision-making, rather than a motor preference under uncertainty. Also, if we assumed the monkeys opted for easier awayIF saccades, we reasoned that toIF saccades in the decision task should be harder to make and therefore slower, than saccades in the selection task, given that slower saccades indicate reduced vigor 12 . Interestingly, in some cases, the velocity of toIF saccades in the decision task was higher than those in the selection task after muscimol, despite matched metrics (cf., cyan symbols in post in Fig.…”
Section: Decision But Not Selection Accuracy Is Altered After Sc Inacmentioning
confidence: 99%
“…Yet, we still observed a pronounced change in accuracy post-muscimol even for the 36% coherence condition, a finding that is better explained by a change in aspects of decision-making, rather than a motor preference under uncertainty. Also, if we assumed the monkeys opted for easier awayIF saccades, we reasoned that toIF saccades in the decision task should be harder to make and therefore slower, than saccades in the selection task, given that slower saccades indicate reduced vigor 12 . Interestingly, in some cases, the velocity of toIF saccades in the decision task was higher than those in the selection task after muscimol, despite matched metrics (cf., cyan symbols in post in Fig.…”
Section: Decision But Not Selection Accuracy Is Altered After Sc Inacmentioning
confidence: 99%
“…Notably, in children with ASD, we found that damage to the cerebellum is prevalent in lobule VI and parts of lobule VIII (Marko et al 2015), regions that in the macaque are critical for control of saccadic eye movements (Barash et al 1999;Takagi et al 1998). Control of saccades in healthy subjects shows exquisite sensitivity to decision-related variables such as reward prediction error (Sedaghat-Nejad et al 2019) and history of effort expenditure (Yoon et al 2018). Thus marmosets may present a particularly good opportunity to investigate the role of the cerebellum in eye movements, social communication, and neurological diseases such as ASD.…”
Section: Introductionmentioning
confidence: 97%
“…Minimization of an overall performance cost has also been suggested by others to underlie oculomotor behavior (for eye saccades, Harris and Wolpert, 2006 ; Sadaghat-Nejad et al, 2019 ). As the human fovea has a high resolution within only 1° of visual angle, and considerable uncertainty in the retinal periphery, theoretical studies have indicated that the saccadic system aims to optimize speed-accuracy trade-off, to minimize saccade duration at the smallest mean-absolute localization errors ( Harris and Wolpert, 2006 ).…”
Section: Discussionmentioning
confidence: 83%